PERILAKU SPORTIVITAS DAN FAIRPLAY OLAHRAGA - Rachmi Marsheilla Aguss; Eko Bagus Fahrizqi; Fedi Ameraldo; Reza Adhi Nugroho; Imam Mahfud (Universitas Teknokrat Indonesia, 2022)
Fair play is a mental attitude that shows the dignity of chivalry in sports. The value of fair play underlies the formation of attitudes, and then attitudes become the basis of behavior. So it can be concluded that fair play provides equal chances of winning for both teams. This type of research is descriptive research research not intended to test certain hypotheses, but only describes